Report of the High-Level Commission on Carbon Pricing and Competitiveness - Carbon Pricing Leadership Coalition (World Bank, Washington, DC, 2019)
The potentially adverse impact of carbon pricing on the competitiveness of businesses and economies has been a matter of concern to industry and policymakers. It has also been a barrier to progress on carbon pricing. The Carbon Pricing Leadership Coalition launched the High-Level Commission on Carbon Pricing and Competitiveness at its 2018 High-Level Assembly to address the issue. This report showcases dialogue among business leaders to explore the evidence base, the concerns of business, and the lessons learned in the design and implementation of carbon pricing policies in the context of competitiveness.